Focal chronic inflammatory demyelinating polyradiculoneuropathy: Onset, course, and distinct features. Issue 2 (16th March 2021) - Benoit, Charline; Svahn, Juliette; Debs, Rabab; Vandendries, Christophe; Lenglet, Timothée; Zyss, Julie; Maisonobe, Thierry; Viala, Karine
Abstract: Focal chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is defined as involving the brachial or lumbosacral plexus, or one or more peripheral nerves in one upper or one lower limb (monomelic distribution). However, other auto‐immune neuropathies such as Lewis‐Sumner syndrome (LSS) and multifocal motor neuropathy (MMN) can also have a focal onset. From a retrospective cohort of 30 focal CIDP patients with a monomelic onset dating back at least 2 years, we distinguished patients with plexus involvement (focal demyelinating plexus neuropathy [F‐PN], n = 18) from those with sensory or sensorimotor (F‐SMN, n = 7), or purely motor (F‐MN, n = 5) impairment located in one or several peripheral nerves. Few (39%) F‐PN patients had motor nerve conduction abnormalities, but the majority showed proximal conduction abnormalities in somatosensory evoked potentials (80%), and all had focal hypertrophy and/or increased short tau inversion recovery image signal intensity on plexus MRI. Impairment remained monomelic in most (94%) F‐PN patients, whereas abnormalities developed in other limbs in 57% of F‐SMN, and 40% of F‐MN patients ( P = .015). The prognosis of F‐PN patients was significantly better: none had an ONLS score > 2 at the final follow‐up visit, vs 43% of F‐SMN patients and 40% of F‐MN patients ( P = .026). Our findings from a large cohort of focal CIDP patients confirm the existence of different entities that are typically categorized under this one term: on the one hand, patients with a focal plexus neuropathy and on the other, patients with monomelic sensori‐motor or motor involvement of peripheral nerves. These two last subgroups appeared to be more likely to evolve to LSS or MMN phenotype, when F‐PN patients have a more distinctive long‐term, focal, benign course.